Identification of Common Bean Genotypes with Dual Leaf And Pod Resistance to Common Bacterial Blight Disease in Uganda - Alladassi, B.M.E.; Nkalubo, S.T.; Mukankusi, C.; Kayaga, H.N.; Gibson, P.; Edema, R.; Urrea, C.A.; Kelly, J.D.; Rubaihayo, P.R. (Crop Science Journal, 2018)
Common Bacterial Blight (CBB), caused by Xanthomonas axonopodis pv. phaseoli (Xap) and Xanthomonas axonopodis pv. phaseoli var. fuscans (Xapf), is a serious disease that affects common bean production worldwide. In Uganda, it is the most severe and widely occurring bacterial disease, causing significant yield losses in common bean. Although various sources of resistance have been developed around the world, none of the varieties grown in Uganda is known to be resistant. The objective of this study was to identify lines with combined leaf and pod resistance for introgression into locally adapted but susceptible Ugandan genotypes. A total of 132 common bean accessions was evaluated in a screenhouse and under field conditions, in an 11x12 alpha lattice design. Genotypes were inoculated with a local isolate in a screenhouse; while the plants were left to undergo natural infestation in field. Results indicated significant differences (P<0.001) in genotypic reactions against the CBB disease, with a range of disease scores of 2.2 - 7.8 on leaves and 2.6 - 7.1 on pods (1-9 CIAT disease scale), suggesting high genetic variability among the tested germplasm. Relatively low correlation (r = 0.39) was observed between leaf and pod reactions, suggesting differential expression of CBB resistance in these two plant organs. Overall, four genotypes, NE2-14-8, NE17-14-29, NE14-09-78 and VAX3, consistently showed resistance in both screenhouse and field evaluations, leaf and pod inoculations and at all sampling stages. These genotypes were, therefore, identified for transferring CBB resistance into Ugandan susceptible market class bean varieties.
Keywords: CBB; Phaseolus vulgaris; Xanthomonas axonopodis